(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This thesis provides information on quality requirements and basic physicochemical and performance properties such as demulsifying, anti-foaming and deaeration, chemical and thermal stability, sulfur content, acidity, purity, flash point, low temperature, viscosity index, lubricity and viscosity of diesel and energy petroleum oils.